Elastic Stable Intramedullary Nailing for Treatment of Pediatric Tibial Fractures - Gurung, Sandeep; KC, Dipendra; Khatri, Roshni (Journal of Lumbini Medical College, 2017)
Introduction: Tibia fractures in the skeletally immature patient can usually be treated with above knee cast or patellar tendon bearing cast. The purpose of our study was to evaluate epidemiology and outcome of Elastic stable intramedullary nailing fixation of pediatric tibial shaft fractures treated at our institution. Methods: Over a period of one year, fifty pediatric patients of tibial shaft fractures, with average age of 9.68 yr (SD=2.37), were treated with elastic stable intramedullary nail. Demographic data, union and complication rate were evaluated. Results: There were 36 closed and 14 open fractures. The average time to union was 11.6 weeks (SD=2.65) for close and 14.3 weeks (SD=2.62) for open fracture. There were no instances of growth arrest, re-manipulations, or re-fracture. Conclusion: We conclude that flexible intramedullary fixation is an easy and effective method of management of both open and closed unstable fractures of the tibia in children. DOI: https://doi.org/10.22502/jlmc.v4i1.82 J. Lumbini. Med. Coll.Vol 4, No 1, Jan-June 2016, Page: 11-14